Novel Plasmid-Mediated Colistin Resistance Gene mcr-3 in Escherichia coli - Wenjuan Yin (American Society for Microbiology, 2017)
ABSTRACT The mobile colistin resistance gene mcr-1 has attracted global attention, as it heralds the breach of polymyxins, one of the last-resort antibiotics for the treatment of severe clinical infections caused by multidrug-resistant Gram-negative bacteria. To date, six slightly different variants of mcr-1, and a second mobile colistin resistance gene, mcr-2, have been reported or annotated in the GenBank database. Here, we characterized a third mobile colistin resistance gene, mcr-3. The gene coexisted with 18 additional resistance determinants in the 261-kb IncHI2-type plasmid pWJ1 from porcine Escherichia coli. mcr-3 showed 45.0% and 47.0% nucleotide sequence identity to mcr-1 and mcr-2, respectively, while the deduced amino acid sequence of MCR-3 showed 99.8 to 100% and 75.6 to 94.8% identity to phosphoethanolamine transferases found in other Enterobacteriaceae species and in 10 Aeromonas species, respectively. pWJ1 was mobilized to an E. coli recipient by conjugation and contained a plasmid backbone similar to those of other mcr-1-carrying plasmids, such as pHNSHP45-2 from the original mcr-1-harboring E. coli strain. Moreover, a truncated transposon element, TnAs2, which was characterized only in Aeromonas salmonicida, was located upstream of mcr-3 in pWJ1. This ΔTnAs2-mcr-3 element was also identified in a shotgun genome sequence of a porcine E. coli isolate from Malaysia, a human Klebsiella pneumoniae isolate from Thailand, and a human Salmonella enterica serovar Typhimurium isolate from the United States. These results suggest the likelihood of a wide dissemination of the novel mobile colistin resistance gene mcr-3 among Enterobacteriaceae and aeromonads; the latter may act as a potential reservoir for mcr-3. IMPORTANCE The emergence of the plasmid-mediated colistin resistance gene mcr-1 has attracted substantial attention worldwide. Here, we examined a colistin-resistant Escherichia coli isolate that was negative for both mcr-1 and mcr-2 and discovered a novel mobile colistin resistance gene, mcr-3. The amino acid sequence of MCR-3 aligned closely with phosphoethanolamine transferases from Enterobacteriaceae and Aeromonas species originating from both clinical infections and environmental samples collected in 12 countries on four continents. Due to the ubiquitous profile of aeromonads in the environment and the potential transfer of mcr-3 between Enterobacteriaceae and Aeromonas species, the wide spread of mcr-3 may be largely underestimated. As colistin has been and still is widely used in veterinary medicine and used at increasing frequencies in human medicine, the continuous monitoring of mobile colistin resistance determinants in colistin-resistant Gram-negative bacteria is imperative for understanding and tackling the dissemination of mcr genes in both the agricultural and health care sectors.